2023
DOI: 10.3390/medicina59061004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pelvic Floor Muscle Training on Quality of Life in Women with Urinary Incontinence: A Systematic Review and Meta-Analysis

César Adrián Curillo-Aguirre,
Enrique Gea-Izquierdo

Abstract: Background and Objectives: Urinary incontinence (UI) is a condition that is more common in women than men and has an increasing prevalence with age. It provides a range of psychological and physical burdens that negatively affect the patient’s quality of life (QoL). However, the economic burden for the healthcare system is being augmented due to the increasing life expectancy of the population. This article aims to identify the effectiveness of pelvic floor muscle training (PFMT) on the QoL in women with UI. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…One of the conservative methods widely used is pelvic floor muscle (PFM) exercises, which have long been identified as the first line of treatment for urinary incontinence [8]. This has been supported by several studies, which have found that PFM exercises have a significant positive effect in women suffering from urinary incontinence [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…One of the conservative methods widely used is pelvic floor muscle (PFM) exercises, which have long been identified as the first line of treatment for urinary incontinence [8]. This has been supported by several studies, which have found that PFM exercises have a significant positive effect in women suffering from urinary incontinence [9][10][11].…”
Section: Introductionmentioning
confidence: 99%